Effect of intermediate airway management on ventilation parameters in simulated paediatric out-of-hospital cardiac arrest: a multicentre randomised crossover trial - Loric Stuby; Laurent Bourgeois; Jean-Marie Tinembart; Elisa Mühlemann; David Thurre; Johan N. Siebert; Laurent Suppan (Swiss Medical Weekly)
INTRODUCTION: Paediatric out-of-hospital cardiac arrest survival rates remain low despite advancements in resuscitation science. Prompt restoration of oxygenation is crucial for achieving return of spontaneous circulation. Delays in airway management are associated with decreased survival rates. The primary objective of this study was to determine whether early i-gel® insertion, without prior bag-valve-mask, could enhance ventilation parameters in comparison with a bag-valve-mask-only approach.